ANALISIS DAN STRATEGI MENINGKATKAN KEPUASAN MAHASISWA IPB TERHADAP PENYELENGGARAAN AKADEMIK - Retnaningsih, Retnaningsih; Simanjuntak, Megawati; Khairati, Amalia (Jurnal Ilmu Keluarga dan Konsumen, 2009)
Consumer is the determinant factor for the quality of services. Students as the one of stakeholders of Bogor Agricultural University (IPB) needed to be given the best services. The aimed of this research were to analyze students satisfaction on academic performance in Bogor Agricultural University (IPB) as well as the strategy to improve students satisfaction. The design of this research was cross sectional study, which carried out in IPB campus, Darmaga-Bogor, West Java for six months since September 2006 to February 2007. Number of samples were 600 students. The result showed that the atributs which needed to be improve in input stage were curriculum appropriateness with the expected competency and system information of incoming students by IPB and department. Meanwhile, on process stage the main priorities to be improved were the appropriateness of material lecture with current condition, the examples used to explain the lecture material, method of delivering lecture material orally, audio-visual equipment, teacher’s effort to make learning process lively, the ease of students to write down and understanding the lecture material, the implementation of learning process evaluation, administrative services in preparation class, teachers and students interaction, grade announcement, last assignment preparation including field study, last assignment administration, passing letter process in faculty, the convenience and cleanness of class, the appropriateness of number tools with number of students in laboratory, field work facility, references collection and the ease of references searching in library, last assignment and middle assignment scheduling, transcript of semester emerging, and also administration services. Whereas in output stage, decision making ability and planning implementation became main priority.